Families' Orientation of Children towards Science and Children's Perception of Science - Bal, Emine; Kaya, Gökhan (Yuzuncu Yil Universitesi Egitim Fakultesi Dergisi, 2024)
This study aimed to examine the levels of families directing their children towards science and children's perception of science in a holistic framework. The research was conducted using mixed methods. Using criterion and convenience sampling methods, 168 parents with preschool children constituted the study group. The study group in the qualitative dimension of the research included 11 families with children between the ages of 3-6 and their children. Three different data collection tools were used in the study. A 5-point Likert-type, 18-item, 3-factor scale developed by Bal and Kaya (2022) was used as a quantitative data collection tool. As a qualitative data collection tool, a 6-question structured interview form developed by the researcher and drawings obtained from children were used. As a result of the study, it was determined that the level of families' orientation of children towards science differed significantly according to the variables of education level and child age, and the level of families' orientation of children towards science had a significant effect on children's perception of science.
Keywords: preschool period; bilim algısı; okul öncesi dönem; bilim; family orientation; science capital; Education (General); aile yönlendirmesi; L7-991; science; 4. Education